LES FRACTURES DE L’OS ZYGOMATIQUE AU CHU SYLVANUS OLYMPIO DE LOME : A PROPOS DE 152 CAS. - Bissa H.; Amana P.; Pegbessou PE.; Kpémissi E.; Amaglo KJ.; Darré T. (European Scientific Journal, ESJ, 2015)
Background: fractures of the zygomatic complex are a fairly common phenomenon in the practice of maxillo-facial traumatology and are a major problem or therapeutic management due to possible functional and aesthetic complications. The purpose of this study was to report the different epidemiological, clinical and therapeutic aspects of fractured zygoma in Lomé. Methods: A 10-year retrospective audit was undertaken of all hospitalized patients, at the department of ENT and Cervico-maxillofacial surgery in Sylvanus Olympio teaching Hospital of Lomé (Togo), who had sustained a fractured zygoma from 2004 to 2013. Results: A total of 152 fractures were sustained and representing 5.4% of all the patients of the department. The average age of the patient was 34 years. The sex distribution is markedly higher for males than for females (6.6/1). Road traffic accidents (88.8%) were the main etiology and motorcycle accident (42.76%) were predominant. Tetrapod fractures (61.18%) were the most frequent type of fractures. In 16,44% of cases fracture of zygoma were not associated with another fracture. Cases were managed by either closed (50%) or open (48.90%) reduction. Percutaneous reduction described by Ginestet (60.43%) was the commonest technique employed for closed treatment and transosseous wiring (66.29%) was the most frequently employed fixation for open reduction Conclusion: fractures of the zygomatic bone are relatively frequent interesting young and male people, due to traffic accidents. Road safety must be respected and the open reduction treatment increasd.